EFFECT OF SEASONS AND MULBERRY VARIETIES ON THE FEED CONVERSION EFFICIENCIES OF DIFFERENT SILKWORM HYBRIDS OF BOMBYX MORI L. - RAMAN, K.V. ANANTHA; MALA, V.R.; MAGADUM, S.B.; DATTA, R.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1995)
Feed effieincy studies were conducted using three improved silkworm hybrids of Bombyx mori L. and six mulberry varieties. The studies were conducted in winter, summer and monsoon seasons in tropical climate. The results were discussed in the light of productivity. S34 and S13 mulberry varieties appear to be superior over the other mulberry varieties tested presently. The hybrid PMX NB4D2 is efficient compared to other improved varieties studied.